Semantic Change in African American Slang - Widawski, Maciej (Studia Anglica Posnaniensia, 2013)
Semantic change is an important part of African American slang and involves two mechanisms: figuration and shifting. Both are enormously productive and account for numerous slang expressions based on standard English. This paper presents these processes in detail. Partially drawing from the author’s earlier publications, the presentation is based on lexical material from a sizable database of citations from contemporary African American sources collected through extensive fieldwork in the United States in recent years.